1993
DOI: 10.1002/aja.1001970206
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of early topographic organization in the embryonic olivocerebellar projection: A model system for the study of pattern formation processes in the central nervous system

Abstract: Many projection systems within the peripheral and central nervous system are topographically organized, and it has become increasinging clear that interactions which occur during development determine the projection patterns these systems exhibit in the adult. The olivocerebellar system was chosen as a model system for this study of afferent pattern formation because it has several characteristics which lend themselves to a study of this type. Applications of horseradish peroxidase were made to both the cerebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…Phenotypically heterogeneous subpopulations of Purkinje and inferior olivary neurons are independently generated by intrinsic genetic programs (Wassef and Sotelo, 1984;Wassef et al, 1990Wassef et al, , 1992aOberdick et al, 1993;Millen et al, 1995) and a similar phenomenon likely occurs also in the deep nuclei (Chédotal et al, 1996). The basic organisation of the olivocerebellar projection is already achieved before any contact with target neurons is established through the selective segregation of ingrowing olivocerebellar axon subsets Chédotal and Sotelo, 1992;Paradies and Eisenman, 1993). Then, reciprocal recognition by phenotypically distinct subpopulations of afferent axons and target neurons in the cerebellar cortex and deep nuclei underlies the formation of the topographically arranged olivo-cortico-nuclear loops which subserve cerebellar function (Lliná s and Welsh, 1993).…”
Section: Terminal Distribution Of the Newly Formed Projectionmentioning
confidence: 95%
“…Phenotypically heterogeneous subpopulations of Purkinje and inferior olivary neurons are independently generated by intrinsic genetic programs (Wassef and Sotelo, 1984;Wassef et al, 1990Wassef et al, , 1992aOberdick et al, 1993;Millen et al, 1995) and a similar phenomenon likely occurs also in the deep nuclei (Chédotal et al, 1996). The basic organisation of the olivocerebellar projection is already achieved before any contact with target neurons is established through the selective segregation of ingrowing olivocerebellar axon subsets Chédotal and Sotelo, 1992;Paradies and Eisenman, 1993). Then, reciprocal recognition by phenotypically distinct subpopulations of afferent axons and target neurons in the cerebellar cortex and deep nuclei underlies the formation of the topographically arranged olivo-cortico-nuclear loops which subserve cerebellar function (Lliná s and Welsh, 1993).…”
Section: Terminal Distribution Of the Newly Formed Projectionmentioning
confidence: 95%
“…Several of the PC-specific markers which are expressed heterogeneously during cerebellar development are not upregulated until late in embryonic development or after birth. By this time the basic parasagittal organization of at least one afferent, the olivocerebellar (OC) projection, is already established (Paradies and Eisenman, 1993). In addition, until recently it has been technically difficult to evaluate the spatial relationship between particular subsets of afferent fibers and specific groups of PC.…”
mentioning
confidence: 99%
“…The location of labeled olivocerebellar fiber terminals originating from the caudal medial accessory olive (cMA0) was compared to the mediolateral positions of groups of L7llacZ+ PC at E17118, the earliest developmental time when P-galactosidase (Pgal) activity can be visualized using X-gal histochemistry. The cMAO projection was selected for comparison to the L7llacZ expression pattern because previous studies had demonstrated that, as in the adult, the embryonic cMA0 projects almost exclusively to the contralateral medial cerebellar cortex (Paradies and Eisenman, 1993). Because L7ilacZ is upregulated first in medial cerebellar regions, the projection from the cMAO was considered the most likely to overlap or colocalize with these populations of labeled cells.…”
mentioning
confidence: 99%
“…These processes include lobule formation, zonal patterning of zebra-striped compartments, and climbing fiber synaptogenesis. In mice, climbing fiber and mossy fiber afferents have already invaded the cerebellum by around embryonic days 13/14 (Grishkat and Eisenman 1995;Paradies and Eisenman 1993). Later, in the cerebellum of older embryos and newborn pups, multiple climbing fibers innervate a single Purkinje cell.…”
mentioning
confidence: 99%